Organização e desenvolvimento do trabalho escolar no contexto de implementação da proposta de reestruturação curricular do ensino médio da SEDUC/RS - Zambon, Luciana Bagolin (2015)
We aim with this research is understand the processes of organization and development of school work in the context of implementation of the proposal for high school curriculum restructuring of SEDUC/RS (PREM/RS) in public high school of the RS. To this end, we propose to answer the following research problem: What opportunities are presented to the stabilization of changes introduced in the organization and development of school work within the implementation process of the PREM/RS? As information sources we used subject: subject (Integrated Seminar teachers, high school teachers and members of management teams of schools) and documents (basic documents of PREM/RS). As instruments to collect information we used focus group, interview and script for textual analysis of documents. We did 03 focus group with 20 teachers of SI and 34 interviews with 13 education coordinators, 20 SI Teachers (some grouped) and 06 high school teachers, acting in 20 schools of the 8th Regional Coordination of Education SEDUC/RS. By these analyzes, we can say: The school work was impacted by PREM/RS by adding new actions to implement the SI, considerably affecting the work of education coordinator and SI teachers; About changes in the evaluation, school work was affected by the redefinition of the usual class councils, performing them at the end of each trimester and bringing together teachers by subject area; We identified structural, operating, professional, personal and cultural factors hampered or hindered the implementation process of the PREM/RS, such as lack of time to study, planning lessons and regular meetings between teachers, teacher resistance changes in the evaluation and the curriculum of high school, individualism in the development of teaching, haste implementation of the proposal by SEDUC/RS, insufficiency of continuing education conducted by SEDUC/RS to ensure the understanding of the proposal, precarious physical structure and lack of resources to carry out SI activities; The immobilization oh the system favored a redefinition of the SI, turning it into isolated subject that occur basically parallel to other subjects; There are individual actions of some teachers towards change in teaching practices, but this has not been reflected in changes in school work. The results indicate the coexistence of two schools of high school with absolutely different purposes, living both in each school: one that continues to work in favor of a teaching preparatory for higher education, and one that begins to worry about a integral formation of young people.